PENGEMBANGAN KIT PRAKTIKUM DIFRAKSI DAN INTERFERENSI CAHAYA UNTUK MENINGKATKAN PENGUASAAN KONSEP DAN KEMAMPUAN BERPIKIR KRITIS - Asep Setiawan; Indarini Dwi Pursitasari; Hendardi Hardhienata (Edusentris, 2019)
This study aims to develop diffraction and light interference practicum kits to improve the mastery of concepts and students' critical thinking skills. The research method begins with needs analysis, design, expert validation, testing to students, and application of practicum kits in learning. The instruments used were expert validation sheets, concept mastery tests and critical thinking skills, observation sheets of teacher and student activities, and student response questionnaires. The results of the study showed the validator's assessment for the content validity aspect and construct validity practicum kit was 91.3%. As well as the N-gain from the initial test and the final test mastery of the concept of 42% (sufficient category) and critical thinking ability by 45% (sufficient category). Inferential statistical test results show that there were significant differences between the initial test scores and the final test of mastery of concepts and critical thinking skills. This result was supported by student response questionnaire after learning with an assessment of 97.3%.